Long-term effects of chlorine stress on the growth and biochemical indices of Cyclina sinensis - Chaohua Wang; Chaohua Wang; Chaohua Wang; Guoliang Ren; Guoliang Ren; Shiyu Yan; Shiyu Yan; Shiyu Yan; Guolong Zhou; Guolong Zhou; Guolong Zhou; Zhengyi Li; et al. (Frontiers in Marine Science)
Chlorine in seawater is toxic to bivalves. This study explored the long-term effects of 20 mg/L, 40 mg/L, and 60 mg/L chlorine on the survival rate, growth, immune, and antioxidant performance of the Cyclina sinensis. After 30 days, neither the 20 mg/L nor 40 mg/L treatment group demonstrated any significant disparity compared with the control group. Nevertheless, significant mortality rates were subsequently observed in all treatment groups. The weight, shell length, and monthly growth rate of C. sinensis in the 60 mg/L group were significantly lower than in the control group (P <0.05). Residual chlorine also triggered the antioxidant stress response mechanism. After 90 days, a significant increase occurred in both the total antioxidant capacity and activity of superoxide dismutase (P <0.05). Chlorine toxicity caused an immune response in the nonspecific immune system of C. sinensis, with alkaline phosphatase and acid phosphatase activities significantly increasing at 30 days and then significantly decreasing (P <0.05). Lysozyme activity also showed a continuous decline after 30 days. These results indicated that C. sinensis was unable to adapt to long-term chlorine toxicity stress but was able to resist chlorine toxicity for a short period (30 days) only when the chlorine concentration was <40 mg/L. Long-term chlorine exposure damaged the immune system of C. sinensis, inhibiting growth and increasing clam mortality. Therefore, in areas where chlorine is used as a disinfectant, the residual chlorine concentration should be tested in the water every 30 days to prevent harm to bivalves caused by long-term chlorine toxicity stress.